Fidelity in complex behaviour change interventions: a standardised approach to evaluate intervention integrity. Issue 11 (15th November 2013) - Mars, Tom; Ellard, David; Carnes, Dawn; Homer, Kate; Underwood, Martin; Taylor, Stephanie J C
Abstract : Objectives: The aim of this study was to (1) demonstrate the development and testing of tools and procedures designed to monitor and assess the integrity of a complex intervention for chronic pain (COping with persistent Pain, Effectiveness Research into Self-management (COPERS) course); and (2) make recommendations based on our experiences. Design: Fidelity assessment of a two-arm randomised controlled trial intervention, assessing the adherence and competence of the facilitators delivering the intervention. Setting: The intervention was delivered in the community in two centres in the UK: one inner city and one a mix of rural and urban locations. Participants: 403 people with chronic musculoskeletal pain were enrolled in the intervention arm and 300 attended the self-management course. Thirty lay and healthcare professionals were trained and 24 delivered the courses (2 per course). We ran 31 courses for up to 16 people per course and all were audio recorded. Interventions: The course was run over three and a half days; facilitators delivered a semistructured manualised course. Outcomes: We designed three measures to evaluate fidelity assessing adherence to the manual, competence and overall impression. Results: We evaluated a random sample of four components from each course (n=122). The evaluation forms were reliable and had good face validity. There were high levels of adherence in the delivery: overall adherence was two (maximum 2, IQR 1.67–2.00), facilitator competence exhibited more variability, and overall competence was 1.5 (maximum 2, IQR 1.25–2.00). Overall impression was three (maximum 4, IQR 2.00–3.00). Conclusions: Monitoring and assessing adherence and competence at the point of intervention delivery can be realised most efficiently by embedding the principles of fidelity measurement within the design stage of complex interventions and the training and assessment of those delivering the intervention. More work is necessary to ensure that more robust systems of fidelity evaluation accompany the growth of complex interventions. Trial Registration ISRCTN No: ISRCTN24426731.